Association of albumin-corrected anion gap with severe consciousness disorders and outcomes in ischemic stroke: a retrospective MIMIC analysis - Ying Chen; Ming-Yao You; Lan Chu (Scientific Reports, 2024)
Abstract The relationship between albumin-corrected anion gap (ACAG) and severe disorder of consciousness (SDOC), in-hospital mortality, and long-term mortality in patients with ischemic stroke (IS) remains unclear. This study investigates the association of ACAG with SDOC and other outcomes in IS using data from the MIMIC-IV database. A total of 2,379 IS patients were included, with a demographic breakdown showing 51% were male and an SDOC incidence of 16.4%. Analysis through Cox proportional hazards models indicated that ACAG is significantly associated with the risks of both SDOC and mortality. Additionally, restricted cubic spline(RCS) analysis suggested a nearly linear relationship between increasing ACAG levels and the incidence of SDOC. Kaplan-Meier curves demonstrated significant differences in the incidence rates of SDOC, in-hospital mortality, and long-term mortality across varying ACAG levels. The findings suggest that ACAG serves as an independent predictor for SDOC, in-hospital mortality, and long-term mortality in IS patients. Nonetheless, further prospective studies are needed to confirm these causal relationships.